2022
DOI: 10.1016/j.isci.2021.103621
|View full text |Cite
|
Sign up to set email alerts
|

Borna disease virus docks on neuronal DNA double-strand breaks to replicate and dampens neuronal activity

Abstract: Summary Borna disease viruses (BoDV) have recently emerged as zoonotic neurotropic pathogens. These persistent RNA viruses assemble nuclear replication centers (vSPOT) in close interaction with the host chromatin. However, the topology of this interaction and its consequences on neuronal function remain unexplored. In neurons, DNA double-strand breaks (DSB) have been identified as novel epigenetic mechanisms regulating neurotransmission and cognition. Activity-dependent DSB contribute critically to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
(110 reference statements)
3
4
0
Order By: Relevance
“…Marty et al . [36] reported that BoDV-1 infection increases primary neuronal DSB levels, which is consistent with our results. However, this study extends those findings by reporting that BoDV-1 infection causes neuronal accumulation of DSBs in vivo in laboratory animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Marty et al . [36] reported that BoDV-1 infection increases primary neuronal DSB levels, which is consistent with our results. However, this study extends those findings by reporting that BoDV-1 infection causes neuronal accumulation of DSBs in vivo in laboratory animals.…”
Section: Discussionsupporting
confidence: 93%
“…Two pieces of evidence support an increase in the number of DSBs: (i) high levels of distinct nuclear foci immunoreactive for γ-H 2 AX [31,32], which is a well-established marker of DSBs, and (ii) upregulated comet tail moment in single cells in comet assays performed at neutral pH [33]. Marty et al [36] reported that BoDV-1 infection increases primary neuronal DSB levels, which is consistent with our results. However, this study extends those findings by reporting that BoDV-1 infection causes neuronal accumulation of DSBs in vivo in laboratory animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4A). As shown previously 55,58 , we confirmed using confocal immunofluorescence microscopy that mature neurons express diffuse 53BP1 staining in their nuclei (Fig. 4Ai , ii & Extended Data Fig.…”
Section: Chronic T Gondii Infection and Systemic Exposure To Il-1b In...supporting
confidence: 88%
“…The genome of bornaviriruses consists of approximately 8900 nucleotides and represents the smallest known genome amongst Mononegavirales. BoDV-1 vSPOTs formed by P protein-driven liquid-liquid phase separation [48], are present in the nucleus, in close interaction with the chromatin, where they dock on neuronal DNA double-strand breaks (DSBs), thereby affecting neuronal epigenetics and activity [49]. In particular, both N and P seem to modulate epigenetic signalling in neurons [50,51].…”
Section: Introductionmentioning
confidence: 99%